Thin Films of Amorphous Hydrogenated Silicon and Solar Modules based on them - V. P. Afanasiev; E. I. Terukov (Известия высших учебных заведений России: Радиоэлектроника, 2016)
Solar energy is one of the most promising sectors of renewable energy. In Russia the mass development of solar energy in connection with the organization launched in February 2015 at "Hevel" production of thin film solar modules based on amorphous silicon, which is intended to create a full-fledged high-tech industry of solar energy as an alternative to traditional energy sources. For support and development of this production open JSC "Scientific and technical center of thin film technology" begin operation at the Ioffe Institute of RAS in 2012, whose main task - improvement of the basic parameters of Solar modules based on amorphous silicon in the interests of "Hevel".